Molecular genetics of essential hypertension - Singh M.; Singh A.K.; Pandey P.; Chandra S.; Singh K.A.; Gambhir I.S. (My University, 2025)
Hypertension is a major public health problem in the developing as well as in developed countries due to its high prevalence and its association with coronary heart disease, renal disease, stroke, peripheral vascular disease, and related disorders. Essential hypertension (EH) is the most common diagnosis in this disease, suggesting that a monocausal etiology has not been identified. However, a number of risk factors associated with EH have also been identified such as age, sex, demographic, environmental, genetic, and vascular factors. Recent advances in molecular biological research had achieved clarifying the molecular basis of Mendelian hypertensive disorders. Molecular genetic studies have now identified mutations in several genes that cause Mendelian forms of hypertension in humans. However, none of the single genetic variants has emerged from linkage or association analyses as consistently related to the blood pressure level in every sample and in all populations. Besides, a number of polymorphisms in candidate genes have been associated with differences in blood pressure. The most prominent candidate has been the polymorphisms in the renin-angiotensin-aldosterone system. In total, EH is likely to be a polygenic disorder that results from inheritance of a number of susceptibility genes and involves multiple environmental determinants. These determinants complicate the study of blood pressure variations in the general population. The complex nature of the hypertension phenotype makes largescale studies indispensable, when screening of familial and genetic factors was intended. In this review, recent genetic studies exploring the molecular basis of EH, including different molecular pathways, are highlighted. © 2016 Taylor & Francis.